1995
DOI: 10.1007/bf00167598
|View full text |Cite
|
Sign up to set email alerts
|

Differential cell count and lymphocyte subsets in bronchoalveolar lavage during pneumonia with and without peripheral neutropenia

Abstract: One hundred immunocompromised HIV negative patients with microbiologically positive pneumonia underwent bronchoalveolar lavage (BAL) studies. Thirty cases showed peripheral neutropenia (< 1000 neutrophils/microL), 70 did not. The total cell number in BAL, the differential cell counts, and the lymphocyte subsets (CD4, CD8, CD19, CD57) were measured. Patients with pneumonia and normal or elevated peripheral neutrophils had a significantly increased total number of cells in BAL compared to patients with periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…aeruginosa strain, as no positive effect was noticed against an O1-LPS strain. In the CP-induced neutropenia model (100mg/kg), the number of granulocytes was reduced about 80% as compared to untreated mice, which is similar to the observed massive leucopenia present in hematopoietic transplantation recipient [25,26] or HIV patients [27]. Despite severe immune suppression, the treatment with Panobacumab resulted in a reduction of bacterial load and inflammation in the lung, indicating that reduced leukocyte numbers might still be sufficient to mediate bacterial clearance after opsonization by Panobacumab.…”
Section: Discussionsupporting
confidence: 63%
“…aeruginosa strain, as no positive effect was noticed against an O1-LPS strain. In the CP-induced neutropenia model (100mg/kg), the number of granulocytes was reduced about 80% as compared to untreated mice, which is similar to the observed massive leucopenia present in hematopoietic transplantation recipient [25,26] or HIV patients [27]. Despite severe immune suppression, the treatment with Panobacumab resulted in a reduction of bacterial load and inflammation in the lung, indicating that reduced leukocyte numbers might still be sufficient to mediate bacterial clearance after opsonization by Panobacumab.…”
Section: Discussionsupporting
confidence: 63%
“…In septic neutropenic patients with infectious pneumonia, BAL is used predominantly to recover alveolar macrophages (AMs). 11,12 Activated AMs can release a wide variety of mediators, most of them capable of damaging the lung alveolar-capillary barrier. [13][14][15][16] Schwartz et al 17 showed in ARDS patients an increased in vivo activation of the nuclear transcriptional regulatory factor nuclear factor B in AMs, which may contribute to the increased expression of various cytokines.…”
mentioning
confidence: 99%